Parameterization of light scattering for solving the inverse problem of determining the concentrations of the principal light scattering and absorbing admixtures in shelf waters - Vadim N. Pelevin (Oceanologia, 2001)
A method for estimating the water backscattering coefficient was put forward on the basis of experimental data of diffuse attenuation coefficient for downwelling irradiance and irradiance reflectance. Calculations were carried out for open sea waters of different types and the spectral dependencies were found ("anomalous" spectra) and explained. On this basis, a new model of light backscattering on particles in the sea is proposed. This model may be useful for modelling remote sensing reflectance spectra in order to solve the inverse problems of estimating the concentration of natural admixtures in shelf waters.